(untitled) (Miscellanea Historico-Iuridica, 2021)
The aim of the article is to present how women’s crime has evolved over the years, whether it has changed or whether it has looked similar in each period. The story is divided into three periods, women’s crime up to 1918, 1918-1939, and 1946-1989, because socio-economic changes in those times were so important that they certainly influenced society. The study presents, as far as possible, trends, structure and dynamics of crime, and also discusses crimes characteristic of women. A paper shows what was characteristic of crime in particular periods, how economic changes affected society and which crimes were most frequently committed by women. The picture of women’s crime from antiquity to 1989 is analysed using official data (crime statistics, court statistics), as well as stories of individual cases, such as witchcraft trials, medieval cases of women accused of adventurism, or the most famous murder in the interwar period - the case of Rita Gorgonowa. The article presents, as far as possible, a historical picture of women’s crime, using various sources. Materials from before the Second World War, and even from the 19th century were used and also the scientific works of the most eminent criminologists of the time. The article was enriched with statistical data from the Ministry of Justice and pre-war statistical yearbooks. This paper uses three research methods, a dogmatic method, literature analysis and the analysis and interpretation of statistical data in order to present a picture of women’s crime in those times as best as possible.